"Older people will die of old age. I'll die of climate change": engaging children and young people in climate decision making for public health - Grace Arnot; Samantha Thomas; Hannah Pitt; Simone McCarthy; Elyse Warner (BMC, 2024)
Abstract Background The climate crisis is a significant risk to the health and wellbeing of children, young people, and future generations. While there are calls for children and young people's engagement in climate decision making, current power structures limit their participation. This paper aimed to understand children's perspectives about the impact of the climate crisis on their futures, their ability to influence climate decisions, and strategies and mechanisms to facilitate their greater engagement in decisions made about the climate crisis. Methods Online in-depth interviews were conducted with n = 28 children (aged 12-16 years) across Australia. Photo elicitation techniques were used to prompt discussion about how the climate crisis impacted their futures, their ability to influence climate decisions, and strategies and mechanisms to engage them in climate decision making. A reflexive approach to thematic analysis was used to construct three themes from data. Images were analysed for ascribed meanings. Results First, participants stated that they and future generations will inherit the climate crisis from older generations, specifically decision makers. Second, they described a need to address a range of age-related barriers that limit children and young people's engagement in climate decision making, including perceptions about their capabilities. Finally, they discussed strategies and mechanisms to embed children and young people's perspectives within climate decision making, including at civic and political levels. Conclusions Children and young people have the right to be involved in decisions made about the climate crisis which significantly impact their futures, including their health and wellbeing. They argue for structural changes to embed their views in climate decision making, and describe a range of engagement strategies and mechanisms to structure their perspectives and knowledge with decision making processes. Furthermore, genuine involvement of children and young people in climate discussions must avoid youthwashing and tokenistic participation. The public health community can help address barriers to youth participation in climate action and should actively engage and collaborate with children and young people to facilitate their political and democratic influence over the climate crisis. This involves making room and creating an accessible seat at the decision making table to ensure their perspectives are embedded in climate decisions.